Upper Fourth At Malory Towers - Blyton, Enid (London, Egmont, 2006)
Darrell and her friends grow together as they share their school days. There are new students to induct, sporting matches to be won, tempers to control and tricks to play on teachers. This work presents stories about life at boarding school as readers follow the girls' lives through 6 years at Malory Towers.
A2 Fiction shelf
Keywords: English Fiction Story